2009
DOI: 10.1002/cncy.20028
|View full text |Cite
|
Sign up to set email alerts
|

Toward a multimodal cell analysis of brush biopsies for the early detection of oral cancer

Abstract: lichen planus mucosae. RESULTS: The stepwise application of 2 additional approaches (morphology, DNA content, argyrophilic nucleolar organizer region counts) increased the specificity of conventional cytologic diagnosis from 92.6% to 100%. This feasibility study provided a proof of concept, demonstrating efficiency,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
0
35
0
1
Order By: Relevance
“…39 Affirming these objections, a recently published study evaluating an oropharyngeal "pap-test p16-Ki67 Dual Stain in HNSCC/Linxweiler et al equivalent" for the screening of oropharyngeal squamous cell carcinoma (OSCC) in high-risk populations could only assign restricted usability of brush biopsy for the sampling of relevant cells in oral precancerous lesions. 40 However, it has repeatedly been shown that swab cytology can be used to confirm the diagnosis of cancer with high sensitivity in OSCC patients, 41,42 the main target group for the diagnostic procedure as proposed in this study because of the relatively high incidence of HPV infection in this entity. 4 Even though surgical biopsy has been considered the gold standard for histomorphological reliability, it is known that this invasive procedure has its own limitations and does not certainly prevent falsenegative results.…”
Section: Ink4amentioning
confidence: 99%
“…39 Affirming these objections, a recently published study evaluating an oropharyngeal "pap-test p16-Ki67 Dual Stain in HNSCC/Linxweiler et al equivalent" for the screening of oropharyngeal squamous cell carcinoma (OSCC) in high-risk populations could only assign restricted usability of brush biopsy for the sampling of relevant cells in oral precancerous lesions. 40 However, it has repeatedly been shown that swab cytology can be used to confirm the diagnosis of cancer with high sensitivity in OSCC patients, 41,42 the main target group for the diagnostic procedure as proposed in this study because of the relatively high incidence of HPV infection in this entity. 4 Even though surgical biopsy has been considered the gold standard for histomorphological reliability, it is known that this invasive procedure has its own limitations and does not certainly prevent falsenegative results.…”
Section: Ink4amentioning
confidence: 99%
“…In der klinischen Anwendung kann die wiederholbare Bürstenbiopsie vor allem bei Schleimhautveränderungen diagnostische Sicherheit geben, die klinisch kontrolliert werden und eine histologische Untersuchung initial nicht indiziert ist. Die Treffsicherheit der Untersuchung hängt von der Kompetenz des Untersuchers ab, sowohl bei der Probeentnahme als auch bei der Auswertung [12]. Aktuellen Forschungsergebnissen zufolge wird in künftigen Untersuchungsstrategien auch das Vorkommen und die Konzentration von charakteristischen Biomarkern im Speichels eine wesentliche Rolle in der Krebsfrüherkennung spielen: insbesondere die Interleukine 6 und 8, die auch im Rahmen der Parodontitis und des Lichen ruber nachweisbar sind, scheinen bei Vorliegen einer malignen Neoplasie deutlich erhöht im Speichel konzentriert zu sein.…”
Section: Supportive Methodenunclassified
“…Exfoliative oral cytology has an increasing role for the evaluation of oral potentially malignant lesions [4] and in recognising dysplasia in suspicious oral lesions with both high sensitivity and specificity [5,6]. The use of auxiliary methods such as DNA image cytometry, AgNOR analysis and cell cycle immunohistochemistry can increase accuracy even further [5,7].…”
Section: Biopsy Techniquesmentioning
confidence: 99%
“…The use of auxiliary methods such as DNA image cytometry, AgNOR analysis and cell cycle immunohistochemistry can increase accuracy even further [5,7]. A biopsy must be performed, however, whenever dysplasia is detected, not only because the architecture needs to be considered when grading lesions but also because invasion cannot be reliably assessed by exfoliative cytology alone.…”
Section: Biopsy Techniquesmentioning
confidence: 99%